Nitrogen and potassium fertigation in coffee at the formation phase, with high plant density - Sobreira, Fabrício Moreira; Guimarães, Rubens José; Colombo, Alberto; Scalco, Myriane Stella; Carvalho, Janice Guedes (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to evaluate the most adequate parceling and dose of nitrogen and potassium for the first and second years of coffee shrub (Coffea arabica) formation, under a drip fertigation system, in southern Minas Gerais, Brazil. Two experiments with high plant density (6.666 plants ha-1) were carried out simultaneously: in one of them, the fertilization was done in 4 applications yearly, and in the other one, in 12 applications. A randomized block design was used with five treatments and four replicates in both experiments. Treatments consisted of N and K2O doses applied via fertigation: 70, 100, 130, 160 and 190% from the N and K2O recommended doses for the rainfed cropping. A control treatment was carried out in rainfed conditions and fertilized with the standard dose (100%). In the first and second years, in both parceling types, there were no significant differences among doses regarding coffee shrub vegetative growth. Parceling into 12 applications is more suitable for fertilization at both first and second years after planting. Fertigated coffee shrubs at the formation phase have higher growth and demand less nitrogen and potassium fertilization than the ones in rainfed conditions.